Suicide Ideation and Thwarted Interpersonal Needs Among Psychiatric Inpatients: A Network Approach. (November 2021) - Brown, Sarah L.; Marshall, Andrew J.; Mitchell, Sean M.; Roush, Jared F.; Mumma, Gregory H.; Jahn, Danielle R.; Ribeiro, Jessica D.; Joiner, Thomas E.; Cukrowicz, Kelly C.
We aimed to demonstrate the utility of an item-level network analysis approach to suicide risk by testing the interpersonal psychological theory of suicide (IPTS) among 402 psychiatric inpatients. We hypothesized that specific thwarted belongingness (TB) or perceived burdensomeness (PB; Interpersonal Needs Questionnaire items) facets would positively relate to passive or active suicide ideation and that these facets would positively relate to each other and form distinct clusters. We also tested TB and PB facets central to the networks as predictors of suicide ideation compared with the full TB and PB subscales. Face-valid items congruent with latent constructs proposed by the IPTS (i.e., feelings of burden on society, feeling that one does not belong) were the only two facets uniquely predictive of passive and active suicide ideation. Facets of TB and PB did not form distinct clusters. Item-level network analysis may have important conceptual, assessment, predictive, and clinical implications for understanding suicide risk.